Betung bamboo-based activated carbon bioadsorbent for the separation of hydrogen-methane gas mixture - Sudibandriyo Mahmud; Oratmangun Melody (E3S Web of Conferences, 2018)
Hydrogen recovery from off gas of hydrocracking and hydrotreating unit is one of the crucial processes in an oil and gas refinery unit as this process helps in lowering the expenses for operations. This study aims to obtain activated carbon that is made from Betung bamboo which can be used as the adsorbent in this process. The activated agents used are H3PO4 and K2CO3, respectively. Each activation lasts for 30 minutes. The results of the characterization test shows that the Iodine number of the activated carbon produced reaches 916.4 mg/g with BET surface area of 465.2 m2/g. SEM-EDX analysis shows that the carbon content is 74.83%. The activated carbon obtained is used to separate Hydrogen and Methane from its mixture at 10, 20 and 30oC with pressure variations of 1 - 6 bar. The results indicate that the maximum number of moles adsorbed from CH4(21.5%)/H2 gas mixture is 0.247 mmol/g, that has been carried out at 6 bar with temperature of 10oC. Methane has 2.2 times higher adsorption capacity than hydrogen, therefore, the Betung bamboo based activated carbon produced from this research can be applied as the adsorbent in the separation process of CH4/H2 mixture and it fits the Langmuir model.